The overlooked burden: anxiety and depression in patients with tuberculosis - Stjepanović, Mirjana; Golubović, Aleksa; Marković, Filip; Milivojević, Ivan; Golubović, Olga; Djordjevic, Jelena (The Journal of Infection in Developing Countries, 2026)
Background: Tuberculosis (TB) is a major global cause of infectious disease–related morbidity and mortality. Beyond its physical burden, TB is associated with significant psychological distress. Anxiety and depression are highly prevalent among TB patients but often remain underrecognized and undertreated, despite their negative impact on treatment adherence, disease outcomes, and quality of life. Objective: This review summarizes current evidence on the prevalence, biological mechanisms, treatment-related factors, and psychosocial determinants of anxiety and depression in patients with TB, and highlights the importance of routine mental health screening in integrated TB care. Methodology: A narrative review of the literature was conducted focusing on epidemiology, underlying biological pathways, neuropsychiatric effects of anti-tuberculosis medications, psychosocial risk factors, and validated screening tools for anxiety and depression in TB populations. Results: Depression affects nearly 45% of TB patients, while anxiety is present in 32–38%, with higher prevalence in low- and middle-income countries and among patients with multidrug-resistant TB. Biological mechanisms include chronic inflammation, cytokine-mediated neuroinflammation, hypothalamic–pituitary–adrenal axis dysregulation, altered tryptophan metabolism, and neuropsychiatric effects of medications such as isoniazid and cycloserine. Psychosocial factors, including stigma, social isolation, poverty, and limited social support, further contribute to psychological distress. Screening tools such as PHQ-9, GAD-7, HADS, and Zung SAS have demonstrated feasibility and validity in TB settings. Conclusions: Anxiety and depression in TB result from interacting biological, pharmacological, and psychosocial factors. Integrating systematic and repeated mental health screening into routine TB care is essential to improve detection, support timely interventions, enhance adherence, and optimize treatment outcomes.